Efficacy of single and multiple doses of fenbendazole against gill parasites (Dactylogyrus sp.) of Labeo rohita (Hamilton, 1822) and its physio‐metabolic effects on the fish. (29th December 2019) - Gupta, Gyandeep; Chatterjee, Arunava; Kumar, Munish; Sardar, Parimal; Varghese, Tincy; Srivastava, Prem Prakash; Gupta, Subodh
Abstract: The study was conducted to investigate the efficacy and physio‐metabolic responses of single and multiple doses of fenbendazole (FBZ) in Labeo rohita against gill parasite ( Dacylogyrus sp.). Two Isoenergetic (395 Kcal DE/100 g) and isonitrogenous (35% CP) purified diets viz. control (without FBZ) and treatment (0.2% FBZ) were prepared. The efficacy of FBZ was measured after administration of single dose (20 mg/kg b. wt.) on 0th day and multiple doses of FBZ, that is, 20 mg/kg b. wt. on 0th, 3rd and 7th day through diet. Although oral administration of FBZ at single dose could significantly reduce the parasite in fish in comparison with the control group, 100% efficacy of the drug was not achieved up to 15th day of treatment. On the other hand, multiple doses of FBZ could show almost 100% efficacy on 15th day in terms of elimination of parasites from gill. The drug induced oxidative stress in examined fish. There was no significant change in activities of hepatic and muscle aspartate aminotransferase and alanine aminotransferase of L. rohita up to 15th day after oral administration of FBZ at single dose. But both single and multiple doses of FBZ could significantly enhance the hepatic superoxide dismutase, catalase and glutathione‐S‐transferase activities in fish up to 7th day of drug administration and significantly decreased thereafter up to 15th and/or 30th day. It is concluded that oral administration of FBZ at multiple doses (20 mg/kg b. wt.) on 1st, 3rd and 7th day could be effective against Dactylogyrus sp. infection in L. rohita .